Effectiveness of the al-Miftah lil Ulum Method in Enhancing Yellow Book Reading Competence at Madrasah Diniyah in Papua - Fardan Abdillah M; Ulil Albab Al Jawad; Azizul Hakim (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study investigates the effectiveness of the al-Miftah lil Ulum method in enhancing students’ proficiency in reading classical Islamic texts (Yellow Book) at Madrasah Diniyah Roudlotul Khuffadz in Sorong, Southwest Papua—a region where Muslims comprise only 38% of the population, as reported by the Ministry of Religious Affairs. The research aims to address the educational challenges faced by Islamic institutions in minority-Muslim contexts. A quasi-experimental design with a quantitative approach was employed. Forty students were selected and divided equally into experimental and control groups (20 students each). The experimental group received instruction using the al-Miftah lil Ulum method, while the control group followed conventional teaching methods. A pre-test and post-test were administered, and the results were analyzed using a paired t-test to assess the method’s impact. Findings indicated a statistically significant improvement in the reading proficiency of the experimental group. The t-test yielded a significance value of 0.000 (p 0.05), confirming the effectiveness of the al-Miftah lil Ulum method. Improvements were noted in reading accuracy, recognition of grammatical structures, and interpretation of classical texts. The results highlight the pedagogical benefits of the al-Miftah lil Ulum method in Muslim-minority regions. It serves as a practical and effective approach for strengthening students’ abilities to comprehend traditional Islamic literature. The al-Miftah lil Ulum method significantly enhances students' Yellow Book reading skills and offers a valuable instructional model for religious education in minority-Muslim settings.